Effect of Coloading Ringer Lactate on Blood Pressure Stability in Patients with Spinal Anesthesia - Noprianty, Richa; Sijabat, Togi Riki Rikardo; Satriyanto, Muhammad Dwi; Valiani, Cici (JAI (Jurnal Anestesiologi Indonesia), 2025)
Background: The most common hemodynamic complication associated with spinal anesthesia is hypotension, hence the need for fluid coloading.Objective: The purpose of this study was to determine the effect of lactated ringer coloading fluid on blood pressure stability.Methods: This study was conducted using a quantitative method with a quasi-experimental design with a one-group pretest-posttest design. This study was conducted at X Hospital in the West Java region from March to April 2024. The research was carried out in the operating room after spinal anesthesia and after the administration of Ringer's lactate. The research instrument used an initial blood pressure observation sheet, blood pressure after spinal anesthesia, and after giving lactated ringer coloading with a calculation of 10 cc/kg of patient weight. The population in this study was all patients who underwent spinal anesthesia, and the sample of this study amounted to 60 patients with non non-probability sampling technique with purposive sampling. Data analysis in this study used univariate and bivariate analysis. This study has carried out data normality tests and research ethics. Bivariate analysis in this study used a Paired t-test.Results: The results showed that after spinal anesthesia, most (51.7%) patients had hypotension. After being given lactated ringer coloading, most patients (68.3%) had normal blood pressure. Systolic blood pressure increased by 9,750 mmHg, and diastolic also increased by 6,500 mmHg.Conclusion: This study concludes that lactated ringer coloading has a significant effect on both systolic and diastolic blood pressure stability after spinal anesthesia.